Foreign Terms and Otherness: A Case Study of The Joy Luck Club and Its Chinese and Japanese Translations - Hua Zhu ([sic])
The limitations of Chinese transcription and the domination of Chinese scripts in print cause a difficulty in reflecting the otherness of Chinese foreign terms in English. The discrepancy among Chinese dialects has also brought about challenges. A novel form of translating Chinese foreign terms in The Joy Luck Club was invented in order to improve the representation of otherness. Since the publication of the first Chinese version of the novel, better results have been demonstrated in more recent retranslations of The Joy Luck Club. Fewer deletions and less mistranslation indicate an improvement in the latest retranslations in comparison to the older versions. On the basis of a result-oriented analysis, supported by data and real-time reading experience, this study discusses linguistic and non-linguistic factors in translating Chinese foreign terms in English in The Joy Luck Club into five Chinese and one Japanese version. Reflecting otherness can provide an accurate translation whereas the translator’s visibility can bring flexibility to the work on translation.